Competing endogenous RNAs (ceRNAs): new entrants to the intricacies of gene regulation - Subramanian, Subbaya (Frontiers in Genetics, 2014)
The discovery of microRNAs (miRNAs) has led to a paradigm shift in our basic understanding of gene regulation. Competing endogenous RNAs (ceRNAs) are the recent entrants adding to the complexities of miRNA mediated gene regulation. ceRNAs are RNAs that share miRNA recognition elements (MREs) thereby regulating each other. It is apparent that miRNAs act as rheostats that fine-tune gene expression and maintain the functional balance of various gene networks. Thus MREs in coding and non-coding transcripts have evolved to become the crosstalk hubs of gene interactions, affecting the expression levels and activities of different ceRNAs. Decoding the crosstalk between MREs mediated by ceRNAs is critical to delineate the intricacies in gene regulation, and we have just begun to unravel this complexity.